Two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film and preparation method and application thereof

The piezoelectric-optoelectronic composite film of two-dimensional fluorine-lead-based perovskite composite PVDF was prepared by electrospinning, which solved the problem of using expensive raw materials and poor piezoelectric performance in the prior art, achieved efficient and low-cost piezoelectric performance improvement, and had photoelectric detection function.

CN119562751APending Publication Date: 2025-03-04HUBEI UNIV +1

Patent Information

Application Number
CN202411606678.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

In the prior art, the piezoelectric performance using expensive Cs raw materials and piezoelectric sensors is poor and other functions of the sensor are not increased.

Method used

Electrospinning method was used to prepare a piezoelectric-photoelectric composite film of two-dimensional fluorine-based perovskite composite PVDF. By dispersing two-dimensional lead-based perovskite in PVDF solution, the polar β-phase content of PVDF is enhanced, thereby enhancing piezoelectric and photoelectric properties.

Benefits of technology

It realizes a low-cost and controllable piezoelectric-photoelectric composite film preparation, improves the piezoelectric coefficient and electrical output performance, and has the effect of photoelectric detection, which can detect ultraviolet light intensity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119562751A_ABST
    Figure CN119562751A_ABST
Patent Text Reader

Abstract

According to the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film as well as the preparation method and the application thereof, (2-FBA) 2PbCl4 and PVDF are compounded, so that the content of a beta phase with a high piezoelectric constant in PVDF is effectively increased, the voltage output performance of a composite piezoelectric sensor is enhanced, meanwhile, the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film has good performance in the photoelectric aspect, and the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film has good application prospects. And a reliable scheme is provided for a piezoelectric-photoelectric self-powered device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of piezoelectric energy materials, and in particular to a method for preparing a two-dimensional lead-based perovskite and PVDF composite film and its application in piezoelectric-photoelectric sensors. Background Art

[0002] With the development of artificial intelligence in the Internet of Things, various wearable sensors tend to be flexible and miniaturized. At present, most wearable electronic products tend to use self-powered piezoelectric materials or optoelectronic materials to provide electricity. Common piezoelectric materials are divided into inorganic piezoelectric materials and organic piezoelectric materials. PVDF and its copolymers in organic piezoelectric materials have become the preferred materials for building flexible piezoelectric sensors due to their superior flexibility and piezoelectricity, but their piezoelectric performance is poor, so improving their piezoelectric performance has become an important issue that needs to be solved. Perovskite has excellent optoelectronic properties. In recent years, the research on lead-based perovskites has gradually matured. Lead-based perovskites provide new ideas and methods for flexible self-powered sensors due to their outstanding piezoelectric and optoelectronic properties.

[0003] At present, flexible piezoelectric sensors usually construct low-dimensional inorganic piezoelectric materials on flexible substrates or disperse inorganic piezoelectric materials in organic polymer matrices to construct flexible composite piezoelectric materials. Patent CN116018045A discloses a two-dimensional lead-based perovskite piezoelectric material (BA) 2 Cb 2 Br 7 The composite system dispersed in organic piezoelectric polymer-polyvinylidene fluoride (PVDF) combines the advantages of high piezoelectric properties of perovskite and flexibility of PVDF-based piezoelectric polymer, increases the content of β phase with high piezoelectric coefficient in PVDF system polymer, and enhances the performance of flexible piezoelectric sensor. However, this material uses expensive Cs as raw material, cesium bromide 305 yuan / g, and this type of improvement only increases the voltage output capacity of piezoelectric sensor, and does not increase other functions of piezoelectric sensor. Summary of the invention

[0004] In order to solve the deficiencies in the prior art, the present invention provides a two-dimensional fluorine-containing lead-based perovskite composite PVDF (2-FBA) 2 PbCl 4 The preparation method of the PVDF composite film is simple, controllable and low-cost; the composite film has good flexibility; the piezoelectric coefficient of the device is large and the electrical output performance is outstanding. The raw materials are cheap and the photoelectric detection effect is achieved, which can be used to detect the intensity of ultraviolet light.

[0005] A two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film, comprising a PVDF base film and (2-FBA) in the base film 2 PbX4 , wherein FBA represents an organic cation: 2-fluorobenzylamine, Pb represents lead, X represents at least one halide anion, and the (2-FBA) 2 PbX 4 It is composed of 2-fluorobenzylamine cation and [PbX 4 ] 2- Two-dimensional layered perovskite structure composed of anions, the (2-FBA) 2 PbX 4 The mass ratio of PVDF to PVDF is 0.04-0.07:0.5-2.

[0006] A method for preparing a two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film comprises the following steps:

[0007] S1. Add lead halide and 2-fluorobenzylamine to a hydrohalic acid solution, heat and stir until the reaction is complete, cool the solution, let it stand, and then vacuum dry the obtained sample to obtain a two-dimensional lead-based perovskite nanocrystal (2-FBA) 2 PbX 4 ;

[0008] S2. PVDF polyvinylidene fluoride is added to an organic solvent of PVDF, heated and stirred until completely dissolved to obtain a PVDF solution;

[0009] S3. Add the two-dimensional lead-based perovskite nanocrystal obtained in step S1 to the PVDF solution obtained in step S2 to obtain a spinning solution;

[0010] S4. The spinning solution is electrospinned to obtain the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film;

[0011] The organic solvent of PVDF in step S2 is at least one of NMP (N-methylpyrrolidone), DMF (N,N-dimethylformamide), DMSO (dimethyl sulfoxide), DMAc (dimethylacetamide), and TEP (triethyl phosphate).

[0012] The mass ratio of the two-dimensional lead-based perovskite nano single crystal to PVDF is 0.04-0.07:0.5-2.

[0013] In step 4, the electrospinning is carried out under an ambient humidity RH < 30%. During the electrospinning process, the spinning solution propulsion speed is set to 0.008 ml / min. The composite film is collected using a grounded flat electrode. The needle tip with a positive voltage of 12.7 kV is 11 cm away from the flat electrode.

[0014] Application of a two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film in piezoelectric-photoelectric devices.

[0015] A two-dimensional lead-based perovskite composite PVDF flexible piezoelectric-photoelectric device comprises the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film according to claim 1, an electrode on the surface of the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film, and a protective layer outside the electrode, wherein the protective layer is made of transparent material.

[0016] The preparation method of the two-dimensional lead-based perovskite composite PVDF flexible piezoelectric-photoelectric device includes:

[0017] (1) cutting the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film and fixing it on the sample stage of a magnetron sputtering instrument, sputtering a platinum differential electrode on the surface of the film, and connecting a 6 cm copper foil to lead out the electrode;

[0018] (2) The device obtained in the above (1) is encapsulated with the protective layer, and the encapsulated device is placed in a vacuum drying oven to eliminate internal voids.

[0019] Beneficial effects brought by the technical solution of the present invention

[0020] Compared with the prior art, the present invention provides a method for preparing a two-dimensional lead-based perovskite nanosheet single crystal, and composites it with PVDF to prepare a piezoelectric-photoelectric sensor, which has the following advantages and beneficial effects:

[0021] (1) This method belongs to the electrospinning method, which is simple to operate and easy to control the process parameters. It can prepare piezoelectric composite films through simple mechanical propulsion equipment.

[0022] (2) By dispersing two-dimensional lead-based perovskite in PVDF solution, there is an interface interaction zone between perovskite and PVDF. The poly-F substitution of organic cations in perovskite can further increase the number of hydrogen bonds of PVDF. Stronger interface self-polarization promotes more PVDF dipole alignment, prompting PVDF to form a polar β phase. The composite of lead-based perovskite and PVDF effectively increases the polar β phase content of PVDF and enhances the voltage output performance of the composite piezoelectric sensor. At the same time, it has good performance in optoelectronics, providing a reliability solution for piezoelectric-photoelectric self-powered devices, thereby effectively improving the piezoelectric output of the nanogenerator.

[0023] (3) Due to the excellent photoelectric properties of lead-based perovskites, they have great potential in photodetection.

[0024] (4) Piezoelectric-photoelectric devices made of composite films have excellent self-powered characteristics and have great potential for energy supply for small digital devices.

[0025] (5) This invention first discovered two-dimensional lead-based perovskite (2-FBA) 2 PbCl4 In PVDF, it can respond to pressure changes to output voltage and current, while two-dimensional lead-based perovskite (2-FBA) 2 PbCl 4 Individual tests show no piezoelectric effect, or two-dimensional lead-based perovskite (2-FBA) 2 PbCl 4 In other piezoelectric materials, the voltage and current output of the piezoelectric material cannot be significantly changed. The raw materials of the piezoelectric device prepared by the present invention are cheap and easy to obtain, and lead chloride only needs 2 to 3 yuan per gram, and no expensive precious metal is used, which is conducive to promotion and application.

[0026] Note: The solvents of PVDF are: NMP (N-methylpyrrolidone), DMF (N, N-dimethylformamide), DMSO (dimethyl sulfoxide), DMAc (dimethylacetamide), TEP (triethyl phosphate). BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is an optical photo of the composite film prepared in Example 1

[0028] Figure 2 6wt% (2-FBA) 2 PbCl 4 SEM image of lead-based perovskite / PVDF electrospun fiber membrane with particle content;

[0029] Figure 3 XRD diagrams of the lead-based perovskite / PVDF composite films of Comparative Example 1 and Examples 1, 2, 3, 4, and 5;

[0030] Figure 4 PFM diagrams of Comparative Example 1 and Example 1;

[0031] Figure 5 It is the VOC output diagram of comparative example 1 and embodiments 1, 2, 3, 4, and 5;

[0032] Figure 6 Pure PVDF and 6wt% (2-FBA) 2 PbCl 4 Lighting comparison test diagram of composite film device;

[0033] Figure 7 The output voltage of the lead-based perovskite / PVDF composite film prepared in Example 1 under different UV light intensities;

[0034] Figure 8 The output current of the lead-based perovskite / PVDF composite film prepared in Example 1 under different UV light intensities;

[0035] Fig. 9The linear relationship between the output current of the lead-based perovskite / PVDF composite film prepared in Example 1 and the UV light intensity under different UV light intensities;

[0036] Fig.10 VOC output diagram of the lead-based perovskite / PLLA composite film prepared by PLLA and Comparative Example 2. Specific embodiments

[0037] The following is a detailed description of the preparation method and application of a lead-based perovskite composite PVDF film proposed by the present invention in conjunction with the accompanying drawings and examples, as follows.

[0038] Comparative Example 1

[0039] This embodiment is comparative example 1, in which pure PVDF is electrospun into a film by an electrospinning method to prepare a flexible device, and the remaining steps are the same as those in other embodiments.

[0040] (1) Disperse 1 g of PVDF (polyvinylidene fluoride) in 3-5 ml of DMF solution and stir magnetically at 65°C and 600 rap for 3-4 h until completely dissolved.

[0041] (2) The clear and transparent spinning solution obtained in step (1) is loaded into a 5 ml syringe, and the spinning solution propulsion speed is set to 0.008 ml / min. The PVDF film is collected using a grounded flat electrode, and the needle tip with a positive voltage of 12.7 kV is 11 cm away from the flat electrode; during the spinning process, the ambient humidity RH is maintained at <30% to ensure complete evaporation of the solvent.

[0042] (3) Remove the pure PVDF film obtained by electrospinning in step (2) from the flat electrode using tweezers.

[0043] (4) Cut the film obtained in step (3) into 2×3 cm 2 A rectangular film is then fixed on the sample stage of a magnetron sputtering instrument to ensure that the film is flat and parallel to the metal platinum target. A platinum differential electrode is sputtered on the surface of the film and a 6 cm copper foil is connected to lead out the electrode.

[0044] (5) The device obtained in step (4) is encapsulated with PI, and the encapsulated device is placed in a vacuum drying oven again under vacuum for 30 minutes to eliminate internal voids. 33 Under standard test conditions (applied force of 12N and frequency of 30Hz), the PFM image of the PVDF flexible piezoelectric sensor prepared in this comparative example is as follows: Figure 4 As shown in (a) in .

[0045] Example 1

[0046] (1) Weigh 1.028 mmol of PbCl 2 (285.91 mg) was placed in an empty glass bottle with a capacity of 20 ml, and 2.056 mmol of o-fluorobenzylamine (235 ul) was weighed into the glass bottle in a glove box.

[0047] (2) Add 5 ml of concentrated hydrochloric acid to the drug weighed in step (1), and stir magnetically at 80°C and 600 rpm for 2 h until the reactant is completely dissolved to obtain a colorless clear solution.

[0048] (3) The colorless solution obtained in step (2) is slowly cooled to room temperature (25° C.) at a cooling rate of 10° C. / h. After being left overnight, the white single crystals generated at the bottom of the solution are collected.

[0049] (4) The white single crystal obtained in step (3) is placed in a vacuum drying oven and dried at 60° C. for 6 h to obtain a crystalline nanosheet.

[0050] (5) Disperse 1 g of PVDF (polyvinylidene fluoride) in 5 ml of DMF solution and stir magnetically at 65°C and 600 rap for 3 h until completely dissolved.

[0051] (6) 0.06 g of the crystalline nanosheets obtained in step (4) was placed in the solution obtained in step (5), and magnetic stirring was performed for 3 h until the solution was completely dissolved to obtain a colorless, clear and transparent spinning solution.

[0052] (7) The colorless, clear and transparent spinning solution obtained in step (6) was loaded into a 5 ml syringe, and the spinning solution propulsion speed was set to 0.008 ml / min. A grounded flat electrode pair (2-FBA) was used. 2 PbCl 4 / PVDF composite film was used for collection, and the needle tip with a positive voltage of 12.7 kV was 11 cm away from the flat electrode; during the spinning process, the ambient humidity RH was maintained at <30% to ensure complete evaporation of the solvent.

[0053] (8) electrospinning the (2-FBA) obtained in step (7) 2 PbCl 4 The / PVDF composite film was removed from the flat electrode using tweezers.

[0054] (9) Cut the film obtained in step (8) into 2×3 cm 2 A rectangular film is then fixed on the sample stage of a magnetron sputtering instrument to ensure that the film is flat and parallel to the metal platinum target. A platinum differential electrode is sputtered on the surface of the film and a 6 cm copper foil is connected to lead out the electrode.

[0055] (10) The device obtained in step (9) is encapsulated with PI, and the encapsulated device is placed in a vacuum drying oven again under a vacuum environment for 30 minutes to eliminate internal voids.

[0056] The actual picture of the lead-based perovskite / PVDF flexible piezoelectric sensor prepared in this example is as follows Figure 1 As shown, the device surface is smooth and has no obvious holes or bubbles.

[0057] The SEM image of the lead-based perovskite / PVDF composite film prepared in this example is as follows: Figure 2 As shown, the lead-based perovskite particles are uniformly distributed in the PVDF fibers.

[0058] like Figure 4 (b), Piezoelectric output performance of lead-based perovskite / PVDF flexible piezoelectric sensor d 33 =118.6pm / V, which is 3.76 times that of pure PVDF film. Under standard test conditions (applied force of 30N and frequency of 30Hz), the lead-based perovskite composite PVDF flexible piezoelectric sensor prepared in this embodiment has a maximum forward output voltage of 12V and a maximum reverse output voltage of -5V. The piezoelectric output performance is the best among all the different percentages of perovskite particles. Figure 5 shown.

[0059] The lead-based perovskite / PVDF composite film obtained in step 8 of this embodiment 1 and the PVDF film obtained in step 3 of comparative example 1 were subjected to a light comparison test. Without the action of an oscillator and ultraviolet light, the maximum output voltage of the film was only 0.01V. Under the action of an oscillator (applied force of 1.2N, frequency of 10Hz), in the dark and under the irradiation of 245nm ultraviolet light, the voltage output of the pure PVDF film was the same, about 0.05V; 6wt% (2-FBA) 2 PbCl 4 The maximum output voltage of the / PVDF composite film in the dark is 0.18V. Compared with the pure PVDF film, the reason for the improvement is that the addition of lead-based perovskite improves the piezoelectric output of the composite film. Under the action of the exciter (applied force of 1.2N, frequency of 10Hz) and at 245nm, 45μW / cm 2 Under ultraviolet light, (2-FBA) 2 PbCl 4 The maximum output voltage of the PVDF / PVDF composite film is 0.7V, which is significantly higher than the 0.05V of the pure PVDF film (e.g. Figure 6 As shown in the figure), thanks to the excellent optoelectronic properties of lead-based perovskites, it provides new ideas and methods for flexible self-powered sensors.

[0060] Example 2

[0061] (1) Weigh 1.028 mmol of PbCl 2 (285.91 mg) was placed in an empty glass bottle with a capacity of 20 ml, and 2.056 mmol of o-fluorobenzylamine (235 ul) was weighed into the glass bottle in a glove box.

[0062] (2) Add 5 ml of concentrated hydrochloric acid to the drug weighed in step (1), and stir magnetically at 80°C and 600 rpm for 2 h until the reactant is completely dissolved to obtain a colorless clear solution.

[0063] (3) The colorless solution obtained in step (2) is slowly cooled to room temperature (25° C.) at a cooling rate of 10° C. / h. After being left overnight, the white single crystals generated at the bottom of the solution are collected.

[0064] (4) The white single crystal obtained in step (3) is placed in a vacuum drying oven and dried at 60° C. for 6 h to obtain a crystalline nanosheet.

[0065] (5) Disperse 1 g of PVDF (polyvinylidene fluoride) in 5 ml of DMF solution and stir magnetically at 65°C and 600 rap for 3 h until completely dissolved.

[0066] (6) Place 0.04 g of the crystalline nanosheets obtained in step (4) into the solution obtained in step (5), and stir magnetically for 3 h until the solution is completely dissolved to obtain a colorless, clear and transparent spinning solution.

[0067] (7) The colorless, clear and transparent spinning solution obtained in step (6) was loaded into a 5 ml syringe, and the spinning solution propulsion speed was set to 0.008 ml / min. A grounded flat electrode pair (2-FBA) was used. 2 PbCl 4 / PVDF composite film was used for collection, and the needle tip with a positive voltage of 12.7 kV was 11 cm away from the flat electrode; during the spinning process, the ambient humidity RH was maintained at <30% to ensure complete evaporation of the solvent.

[0068] (8) electrospinning the (2-FBA) obtained in step (7) 2 PbCl 4 The / PVDF composite film was removed from the flat electrode using tweezers.

[0069] (9) Cut the film obtained in step (8) into 2×3 cm 2 A rectangular film is then fixed on the sample stage of a magnetron sputtering instrument to ensure that the film is flat and parallel to the metal platinum target. A platinum differential electrode is sputtered on the surface of the film and a 6 cm copper foil is connected to lead out the electrode.

[0070] (10) The device obtained in step (9) is encapsulated with PI, and the encapsulated device is placed in a vacuum drying oven again under a vacuum environment for 30 minutes to eliminate internal voids.

[0071] Example 3

[0072] (1) Weigh 1.028 mmol of PbCl 2 (285.91 mg) was placed in an empty glass bottle with a capacity of 20 ml. In a glove box, 2.056 mmol of o-fluorobenzylamine (235 ul) was weighed into the glass bottle.

[0073] (2) Add 5 ml of concentrated hydrochloric acid to the drug weighed in step (1), and stir magnetically at 80°C and 600 rpm for 2 h until the reactant is completely dissolved to obtain a colorless clear solution.

[0074] (3) The colorless solution obtained in step (2) is slowly cooled to room temperature (25° C.) at a cooling rate of 10° C. / h. After being left overnight, the white single crystals generated at the bottom of the solution are collected.

[0075] (4) The white single crystal obtained in step (3) was placed in a vacuum drying oven and dried at 60°C for 6 h to obtain a crystalline nanosheet.

[0076] (5) Disperse 1 g of PVDF (polyvinylidene fluoride) in 5 ml of DMF solution and stir magnetically at 65°C and 600 rap for 3 h until completely dissolved.

[0077] (6) Place 0.05 g of the crystalline nanosheets obtained in step (4) into the solution obtained in step (5), and stir magnetically for 3 h until they are completely dissolved to obtain a colorless, clear and transparent spinning solution.

[0078] (7) The colorless, clear and transparent spinning solution obtained in step (6) was loaded into a 5 ml syringe, and the spinning solution propulsion speed was set to 0.008 ml / min. A grounded flat electrode pair (2-FBA) was used. 2 PCl 4 / PVDF composite film was used for collection, and the needle tip with a positive voltage of 12.7 kV was 11 cm away from the flat electrode; during the spinning process, the ambient humidity RH was maintained at <30% to ensure complete evaporation of the solvent.

[0079] (8) electrospinning the (2-FBA) obtained in step (7) 2 PbCl 4 The / PVDF composite film was removed from the flat electrode using tweezers.

[0080] (9) Cut the film obtained in step (8) into 2×3 cm 2A rectangular film is then fixed on the sample stage of a magnetron sputtering instrument to ensure that the film is flat and parallel to the metal platinum target. A platinum differential electrode is sputtered on the surface of the film and a 6 cm copper foil is connected to lead out the electrode.

[0081] (10) The device obtained in step (9) is encapsulated with PI, and the encapsulated device is placed in a vacuum drying oven again under a vacuum environment for 30 minutes to eliminate internal voids.

[0082] Example 4

[0083] (1) Weigh 1.028 mmol of PbCl 2 (285.91 mg) was placed in an empty glass bottle with a capacity of 20 ml, and 2.056 mmol of o-fluorobenzylamine (235 ul) was weighed into the glass bottle in a glove box.

[0084] (2) Add 5 ml of concentrated hydrochloric acid to the drug weighed in step (1), and stir magnetically at 80°C and 600 rpm for 2 h until the reactant is completely dissolved to obtain a colorless clear solution.

[0085] (3) The colorless solution obtained in step (2) is slowly cooled to room temperature (25° C.) at a cooling rate of 10° C. / h. After being left overnight, the white single crystals generated at the bottom of the solution are collected.

[0086] (4) The white single crystal obtained in step (3) was placed in a vacuum drying oven and dried at 60°C for 6 h to obtain a crystalline nanosheet.

[0087] (5) Disperse 1 g of PVDF (polyvinylidene fluoride) in 5 ml of DMF solution and stir magnetically at 65°C and 600 rap for 3 h until completely dissolved.

[0088] (6) 0.07 g of the crystalline nanosheets obtained in step (4) was placed in the solution obtained in step (5), and magnetic stirring was performed for 3 h until the solution was completely dissolved to obtain a colorless, clear and transparent spinning solution.

[0089] (7) The colorless, clear and transparent spinning solution obtained in step (6) was loaded into a 5 ml syringe, and the spinning solution propulsion speed was set to 0.008 ml / min. A grounded flat electrode pair (2-FBA) was used. 2 PbCl 4 / PVDF composite film was used for collection, and the needle tip with a positive voltage of 12.7 kV was 11 cm away from the flat electrode; during the spinning process, the ambient humidity RH was maintained at <30% to ensure complete evaporation of the solvent.

[0090] (8) electrospinning the (2-FBA) obtained in step (7) 2 PbCl 4The / PVDF composite film was removed from the flat electrode using tweezers.

[0091] (9) Cut the film obtained in step (8) into 2×3 cm 2 A rectangular film is then fixed on the sample stage of a magnetron sputtering instrument to ensure that the film is flat and parallel to the metal platinum target. A platinum differential electrode is sputtered on the surface of the film and a 6 cm copper foil is connected to lead out the electrode.

[0092] (10) The device obtained in step (9) is encapsulated with PI, and the encapsulated device is placed in a vacuum drying oven again under a vacuum environment for 30 minutes to eliminate internal voids.

[0093] Example 5

[0094] (1) Weigh 1.028 mmol of PbCl 2 (285.91 mg) was placed in an empty glass bottle with a capacity of 20 ml, and 2.056 mmol of o-fluorobenzylamine (235 ul) was weighed into the glass bottle in a glove box.

[0095] (2) Add 5 ml of concentrated hydrochloric acid to the drug weighed in step (1), and stir magnetically at 80°C and 600 rpm for 2 h until the reactant is completely dissolved to obtain a colorless clear solution.

[0096] (3) The colorless solution obtained in step (2) is slowly cooled to room temperature (25° C.) at a cooling rate of 10° C. / h. After being left overnight, the white single crystals generated at the bottom of the solution are collected.

[0097] (4) The white single crystal obtained in step (3) was placed in a vacuum drying oven and dried at 60°C for 6 h to obtain a crystalline nanosheet.

[0098] (5) Disperse 1 g of PVDF (polyvinylidene fluoride) in 5 ml of DMF solution and stir magnetically at 65°C and 600 rap for 3 h until completely dissolved.

[0099] (6) 0.08 g of the crystalline nanosheets obtained in step (4) was placed in the solution obtained in step (5), and magnetic stirring was performed for 3 h until the solution was completely dissolved to obtain a colorless, clear and transparent spinning solution.

[0100] (7) The colorless, clear and transparent spinning solution obtained in step (6) was loaded into a 5 ml syringe, and the spinning solution propulsion speed was set to 0.008 ml / min. A grounded flat electrode pair (2-FBA) was used. 2 PbCl 4 / PVDF composite film was used for collection, and the needle tip with a positive voltage of 12.7 kV was 11 cm away from the flat electrode; during the spinning process, the ambient humidity RH was maintained at <30% to ensure complete evaporation of the solvent.

[0101] (8) electrospinning the (2-FBA) obtained in step (7) 2 PbCl 4 The / PVDF composite film was removed from the flat electrode using tweezers.

[0102] (9) Cut the film obtained in step (8) into 2×3 cm 2 A rectangular film is then fixed on the sample stage of a magnetron sputtering instrument to ensure that the film is flat and parallel to the metal platinum target. A platinum differential electrode is sputtered on the surface of the film and a 6 cm copper foil is connected to lead out the electrode.

[0103] (10) The device obtained in step (9) is encapsulated with PI, and the encapsulated device is placed in a vacuum drying oven again under a vacuum environment for 30 minutes to eliminate internal voids.

[0104] Comparative Example 2

[0105] This embodiment is comparative example 2.

[0106] (1) Weigh 1.028 mmol of PbCl 2 (285.91 mg) was placed in an empty glass bottle with a capacity of 20 ml, and 2.056 mmol of o-fluorobenzylamine (235 ul) was weighed into the glass bottle in a glove box.

[0107] (2) Add 5 ml of concentrated hydrochloric acid to the drug weighed in step (1), and stir magnetically at 80°C and 600 rpm for 2 h until the reactant is completely dissolved to obtain a colorless clear solution.

[0108] (3) The colorless solution obtained in step (2) is slowly cooled to room temperature (25° C.) at a cooling rate of 10° C. / h. After being left overnight, the white single crystals generated at the bottom of the solution are collected.

[0109] (4) The white single crystal obtained in step (3) was placed in a vacuum drying oven and dried at 60°C for 6 h to obtain a crystalline nanosheet.

[0110] (5) Disperse 1 g of PLLA (poly (L-lactic acid)) into 5 ml of DMF solution and stir magnetically at 65°C and 600 rap for 3 h until it is completely dissolved.

[0111] (6) 0.06 g of the crystalline nanosheets obtained in step (4) was placed in the solution obtained in step (5), and magnetic stirring was performed for 3 h until the solution was completely dissolved to obtain a colorless, clear and transparent spinning solution.

[0112] (7) The colorless, clear and transparent spinning solution obtained in step (6) was loaded into a 5 ml syringe, and the spinning solution propulsion speed was set to 0.008 ml / min. A grounded flat electrode pair (2-FBA) was used. 2 PbCl 4 / PLLA composite film was collected, and the needle tip with a positive voltage of 12.7 kV was 11 cm away from the flat electrode; during the spinning process, the ambient humidity RH was maintained at <30% to ensure complete evaporation of the solvent.

[0113] (8) electrospinning the (2-FBA) obtained in step (7) 2 PbCl 4 The / PLLA composite film was removed from the flat electrode using tweezers.

[0114] (9) Cut the film obtained in step (8) into 2×3 cm 2 Then put two pieces of 1.8×2.8cm 2 Aluminum film is pasted to both sides of the rectangular film as electrodes and connected to 6 cm copper foil to lead out the electrodes.

[0115] (10) The device obtained in step (9) is encapsulated with PI, and the encapsulated device is placed in a vacuum drying oven again under a vacuum environment for 30 minutes to eliminate internal voids.

[0116] Comparative Example 3

[0117] This embodiment is comparative example 3, in which pure PLLA is electrospun into a film by an electrospinning method to prepare a flexible device, and the remaining steps are the same as those in other embodiments.

[0118] (1) Disperse 1 g of PLLA (polyvinylidene fluoride) in 3-5 ml of DMF solution and stir magnetically at 65°C and 600 rap for 3-4 h until completely dissolved.

[0119] (2) The clear and transparent spinning solution obtained in step (1) is loaded into a 5 ml syringe, the spinning solution propulsion speed is set to 0.008 ml / min, and the PLLA film is collected using a grounded flat electrode. The needle tip with a positive voltage of 12.7 kV is 11 cm away from the flat electrode; during the spinning process, the ambient humidity RH is maintained at <30% to ensure complete evaporation of the solvent.

[0120] (3) Remove the pure PLLA film obtained by electrospinning in step (2) from the flat electrode using tweezers.

[0121] (4) Cut the film obtained in step (3) into 2×3 cm 2A rectangular film is then fixed on the sample stage of a magnetron sputtering instrument to ensure that the film is flat and parallel to the metal platinum target. A platinum differential electrode is sputtered on the surface of the film and a 6 cm copper foil is connected to lead out the electrode.

[0122] (5) The device obtained in step (4) is encapsulated with PI, and the encapsulated device is placed in a vacuum drying oven again under a vacuum environment for 30 minutes to eliminate internal voids.

[0123] The PLLA flexible piezoelectric sensor prepared in this comparative example and the 6wt% (2-FBA) prepared in comparative example 2 2 PbCl 4 / PLLA device is tested for electrical output, and its output voltage is as follows Fig.10 shown.

[0124] Under standard test conditions (applied force of 30N, frequency of 30Hz), the devices made of lead-based perovskite / PVDF composite films obtained in Comparative Example 1, Examples 1, 2, 3, 4, and 5 were tested for electrical output. 2 PbCl 4 The output voltage of the PVDF device is the highest, reaching 12.2V. Figure 5 As shown. Proof 6wt% (2-FBA) 2 PbCl 4 / PVDF devices have the most outstanding electrical performance.

[0125] The light intensity used is: 5μW / cm 2 、10μW / cm 2 、15μW / cm 2 , 20μW / cm 2 , 25μW / cm 2 、30μW / cm 2 、35μW / cm 2 , 40μW / cm 2 , 45μW / cm 2 The lead-based perovskite / PVDF composite film obtained in step 8 of Example 1 was irradiated with 245 nm ultraviolet light, and the output voltage and current of the composite film were detected under the action of an oscillator (applied force of 1.2 N, frequency of 10 Hz). The results are as follows: Figure 7 is the output voltage of the composite film under different UV light intensities, such as Figure 8 is the output current of the composite film under different UV light intensities. The UV light intensity and the output current of the composite film have the following relationship: Fig. 9 The linear relationship shown is, I = 3.371 + 0.871i, i is the UV light intensity, I is the output current, R 2=0.9974. It can be seen that ultraviolet irradiation can amplify the voltage and current output of the lead-based perovskite / PVDF composite film of the present invention. The ultraviolet light intensity under natural sunlight conditions is 200 times the maximum value of the ultraviolet light intensity of the present invention. The voltage output of the lead-based perovskite / PVDF composite film of the present invention under natural sunlight conditions will be amplified by hundreds of times.

[0126] Therefore, the ultraviolet light intensity can be converted from the current or voltage output by the lead-based perovskite / PVDF composite film prepared by the present invention.

Claims

1. A two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film, characterized in that: The invention comprises a PVDF base film and (2-FBA)2PbX4 in the base film, wherein FBA represents an organic cation: 2-fluorobenzylamine, Pb represents lead, and X represents at least one halide anion. The (2-FBA)2PbX4 is composed of 2-fluorobenzylamine cation and [PbX4] 2- The two-dimensional layered perovskite structure is composed of anions, and the mass ratio of (2-FBA)2PbX4 and PVDF is 0.04-0.07:0.5-2.

2. The method for preparing a two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film according to claim 1, characterized in that: The following steps are involved: S1. Add lead halide and 2-fluorobenzylamine to a hydrohalic acid solution, heat and stir until the reaction is complete, cool the solution, let it stand, and then vacuum dry the obtained sample to obtain a two-dimensional lead-based perovskite nanocrystal (2-FBA) 2PbX4; S2. PVDF polyvinylidene fluoride is added to an organic solvent of PVDF, heated and stirred until completely dissolved to obtain a PVDF solution; S3. Add the two-dimensional lead-based perovskite nanocrystal obtained in step S1 to the PVDF solution obtained in step S2 to obtain a spinning solution; S4. The spinning solution is subjected to electrospinning to obtain the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film.

3. The method for preparing a two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film according to claim 2, characterized in that: The organic solvent of PVDF in step S2 is at least one of N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, dimethylacetamide, and triethyl phosphate.

4. The method for preparing a two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film according to claim 2, characterized in that: The mass ratio of the two-dimensional lead-based perovskite nano single crystal to PVDF is 0.04-0.07:0.5-2.

5. The method for preparing a two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film according to claim 2, characterized in that: In step S4, the electrospinning is performed under an ambient humidity RH < 30%, the spinning solution propulsion speed is set at 0.008 ml / min, the composite film is collected using a grounded flat electrode, and the needle tip with a positive voltage of 12.7 kV is 11 cm away from the flat electrode.

6. Application of the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film as claimed in claim 1 in piezoelectric-photoelectric devices.

7. A two-dimensional lead-based perovskite composite PVDF flexible piezoelectric-photoelectric device, characterized in that: It comprises the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film as described in claim 1, an electrode on the surface of the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film and a protective layer outside the electrode, wherein the protective layer is made of transparent material.

8. The method for preparing the two-dimensional lead-based perovskite composite PVDF flexible piezoelectric-photoelectric device according to claim 7, characterized in that: The following steps are involved: (1) Cutting the two-dimensional lead-based perovskite PVDF piezoelectric-photoelectric composite film described in claim 1 and fixing it on the sample stage of a magnetron sputtering instrument, sputtering a platinum differential electrode on the surface of the film, and connecting a copper foil to lead out the electrode; (2) Encapsulating the device obtained in step (1) with the protective layer, and placing the encapsulated device in a vacuum drying oven to eliminate internal voids.

Citation Information

Patent Citations

  • PVDF-based piezoelectric film, preparation method and application thereof, and PVDF-based flexible composite piezoelectric device

    CN116018045A

Cited By

  • Direct X-ray detector based on one-dimensional bismuth-based perovskite material and preparation method

    CN119997784A